Does Early Graft Patency Benefit from Perioperative Statin Therapy? A Propensity Score-Matched Study of Patients Undergoing Off-Pump Coronary Artery Bypass Surgery - Shanglin Chen; Hengchao Wu; Tao Yang; Baotong Li; Yuanyu Hu; Hansong Sun (Cardiovascular Therapeutics)
Background. Decreased graft patency after off-pump coronary artery bypass grafting (OPCAB) leads to substantial increases in cardiac events. However, there is paucity of data on efficacy and safety of perioperative statin therapy for OPCAB populations. Methods. 582 patients undergoing OPCAB in a single-institution database (October 1, 2009–September 30, 2012) were stratified by perioperative continuation of statin therapy (CS group, n=398) or not (DS group, n=184). Inverse probability weighted propensity adjustment was used to account for treatment assignment bias, resulting in a well-matched cohort. Primary outcomes were graft patency at an average of five days after operation and in-hospital mortality. Secondary outcomes included intraoperative blood loss, liver, and renal functions. Results. No in-hospital death occurred in this study. Early graft patency rates after OPCAB were 98.4% (1255 of 1275 grafts) in the CS group and 98.0% (583 of 595 grafts, P=0.486) in the DS group. Secondary outcomes showed a reduction in blood loss during operation (438.53 mL versus 480.47 mL, P=0.01). Continuation of statin therapy is associated with alanine transaminase (ALT) elevation (49.67 U/L versus 34.52 U/L, P<0.001), as well as aspartate transaminase (33.54 U/L versus 28.10 U/L, P<0.001). Abnormal ALT elevation was observed in 8.9% of the CS group and 3.1% in DS (odds ratio 3.06, 95% confidence interval, 1.77 to 5.29, P<0.001). There was no significant difference in estimated glomerular filtration rate (76.28 mL/min/1.73m2 versus 76.13 mL/min/1.73m2, P=0.90). Subgroup analyses suggested that graft occlusion was less common in CS than in DS group among smoking patients (odds ratio 0.41, 95% confidence interval, 0.20 to 0.86, P=0.026). Conclusions. Perioperative continuation of statin therapy did not improve early graft patency in OPCAB patients. A lower risk of graft occlusion was observed among smoking patients. Continuous statin use correlated with liver function elevation (Clinical Trials.gov number, NCT 01268917).